Eksplorasi Implementasi Laboratorium Fisika Berbasis Inquiry Di SMAN 1 Kejayan - Reviandy Azhar Ramdhani; Muhammad Nafis Rojabi; Moch. Chusni Mubarok; Nur Kholis (Program Studi Pendidikan Fisika Universitas Katolik Widya Mandira, 2024)
This study aims to identify and analyze the impact of the implementation of inquiry-based Physics Laboratory on the quality of learning and student learning outcomes in SMAN 1 Kejayan. Specifically, the purpose of this study is to understand how inquiry-based approach affects the understanding of physics concepts, students ' learning motivation, as well as the challenges and opportunities that arise in the process of its implementation. This article explores the implementation of inquiry-based Physics Laboratory in SMAN 1 Kejayan which was previously dominated by qualitative methods that focused on memorization and limited application of physics concepts. The implementation of this method offers the potential to improve the quality of physics learning and students ' learning outcomes by engaging them in hands-on exploration of physics concepts, which increases understanding and motivation for learning. The school supports teachers with the necessary training and laboratory facilities. Research uses a qualitative approach and demonstrates the positive impacts of this approach, such as improved student understanding and learning motivation, although challenges remain, including time management adjustments, teacher training, and resource provision. The implementation of inquiry-based Physics Laboratory in SMAN 1 Kejayan showed a positive impact on the understanding of physics concepts and student learning motivation. Despite challenges in terms of teacher training and resource provision, ongoing support from schools through training and investment in laboratory facilities has proven effective in strengthening these methods. The results indicate that inquiry-based approach can improve the quality of physics learning and student learning outcomes, as well as encourage active participation and involvement of students in the learning process. The study's conclusion states that despite the challenges, this approach supports better learning quality and improved student learning outcomes, with schools continuing to invest in teacher training and laboratory resources to strengthen the application of these methods.